1977
DOI: 10.1042/bst0050290
|View full text |Cite
|
Sign up to set email alerts
|

Properties of [99mTc] Technetium-Labelled Liposomes in Normal and Tumour-Bearing Rats

Abstract: Liposomes (phospholipid vesicles) have been proposed as carriers of materials of therapeutic interest, and work in this area has been reviewed (Tyrrell et al., 1976). The possibility of utilizing such a system in tumour therapy has received some attention, and Gregoriadis et al. (1974) injected patients with liposomes using entrapped l 3 I Ilabelled albumin as a marker. Tissue distribution was measured post mortem, several days after administration. As a more versatile alternative we have been investigating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 1 publication
2
40
0
1
Order By: Relevance
“…The rate of metabolism of the liposomes may be different in the Walker 256 rat tumour used in the animal model described by Richardson et al (1977Richardson et al ( , 1978a and the human tumours. Lack of accumulation of liposomes in the human studies could conceivably be due to a rapid turnover of the liposome components, releasing the 99mTc label from the tumour cells.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The rate of metabolism of the liposomes may be different in the Walker 256 rat tumour used in the animal model described by Richardson et al (1977Richardson et al ( , 1978a and the human tumours. Lack of accumulation of liposomes in the human studies could conceivably be due to a rapid turnover of the liposome components, releasing the 99mTc label from the tumour cells.…”
Section: Discussionmentioning
confidence: 98%
“…There have been two studies, using animal tumour models, showing tumour localization of labelled liposomes (Neerunjun et al, 1977;Richardson et al, 1977) and one study in which no tumour localization was observed (Anghileri et al, 1976). Patient studies have also been reported (Gregoriadis et al, 1974;Segal et al, 1976) but in only one of these (Gregoriadis et al, 1974) has there been a significant tumour accumulation of the liposome label, in a single patient with cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticles (NP & CNP) were labeled separately with 99m Tc pertechnetate by direct labeling method as reported (Richardson et al, 1977). Briefly, freshly eluted 0.1 mL of 99m Tc (185 MBq/mL) was mixed with 0.1 mL stannous chloride solution in 10% acetic acid and the pH of the solution was adjusted to 7.0 using sodium bicarbonate solution.…”
Section: Radiochemical Synthesis Of Technetium-99m ( 99m Tc) Nanopartmentioning
confidence: 99%
“…The use of radiolabeled liposomes in tumor imaging was first done in 1970s (Neerunjun et al 1977;Richardson et al 1977;Hamoudeh et al 2008). Since then with the developing technology in the engineering and computer science, lots of imaging modalities were developed in recent years.…”
Section: Kondo Et Al 2004mentioning
confidence: 99%